PENGGUNAAN MODEL PROBLEM BASED LEARNING BERBANTUAN E-LEARNING TERHADAP KEMANDIRIAN BELAJAR MAHASISWA PADA DIMENSI TIGA - Jusep Saputra (FKIP Universitas Muhammadiyah Prof. DR. HAMKA, 2017)
Self-regulated learning of learners can be achieved, if in the process of learning mathematics provides an open opportunity for students to learn independently. This research is a mixed method type embedded design, which aims to do studies focused on the use of the Problem Based Learning (PBL) model assisted e-learning to student self-regulated learning. Sample selection is done on the purposive sampling and was taken 2 class contracting courses of school math III. Class A numbered 50 members, 24 the superior group and 26 the low group, given the treatment with PBL models assisted e-learning and class B numbered 50, 27 the superior group and 23 the low group, with expository. Instruments used in this research is self-regulated learning questionnaire with Likert scale. Based on data analysis we concluded that (1) Self-regulated learning of superior and low student who obtains aided PBL models assisted e-learning is better than self-regulated learning of superior and low superior students who obtain expository.